2008
DOI: 10.1089/ten.tea.2007.0160
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Drug-Metabolizing Enzyme Genes in Layered Co-Culture of a Human Liver Cell Line and Endothelial Cells

Abstract: Primary human hepatocytes are used extensively to study drug-metabolizing enzymes such as the cytochrome P450 (CYP) enzymes. However, the activities of these enzymes decrease rapidly during culture. In the present study, using a thermo-responsive culture dish, layered co-culture was achieved by placing a bovine pulmonary artery endothelial cell (BPAEC) sheet onto the human hepatoma cell line HepG2. In the BPAEC/HepG2 layered co-culture system, real-time polymerase chain reaction analysis showed that the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…In our previous study, the CYP3A4 activity in the layered co-cultured cells increased 3.4-fold compared to that in the monolayer culture cells. 21) These results indicate that the increased expression of the cytochrome P450 mRNAs correlates with increased CYP enzyme activity.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…In our previous study, the CYP3A4 activity in the layered co-cultured cells increased 3.4-fold compared to that in the monolayer culture cells. 21) These results indicate that the increased expression of the cytochrome P450 mRNAs correlates with increased CYP enzyme activity.…”
Section: Resultsmentioning
confidence: 83%
“…15 previously reported that in the layered co-cultured cells, consisting of a BPAEC sheet overlaid onto HepG2 cells, the gene expression levels of CYP2C9, CYP3A4 and CYP3A7 were significantly increased compared with monolayer cultured HepG2 cells. 21) The results suggested that our co-culture system would be suitable for drug metabolism analysis.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations